MicroRNA as Type I Interferon-Regulated Transcripts and Modulators of the Innate Immune Response - Forster, Samuel C.; Tate, Michelle D.; Hertzog, Paul J. (Frontiers in Immunology, 2015)
Type I interferons (IFNs) are an important family of cytokines that regulate innate and adaptive immune responses to pathogens, in cancer and inflammatory diseases. While the regulation and role of protein-coding genes involved in these responses are well characterized, the role of non-coding microRNAs in the IFN responses is less developed. We review the emerging picture of microRNA regulation of the IFN response at the transcriptional and post-transcriptional level. This response forms an important regulatory loop, several microRNAs target transcripts encoding components at many steps of the type I IFN response, both production and action, at the receptor, signaling, transcription factor and regulated gene level. Not only do IFNs regulate positive signaling molecules, but also negative regulators such as SOCS1. In total, 36 microRNA are reported as IFN regulated. Given this apparent multipronged targeting of the IFN response by microRNAs and their well characterized capacity to “buffer” responses in other situations, the prospects of improved sequencing and microRNA targeting technologies will facilitate the elucidation of the broader regulatory networks of microRNA in this important biological context, and their therapeutic and diagnostic potential.